HUBUNGAN TINGKAT STRES, NAFSU MAKAN DAN POLA MAKAN DENGAN KEJADIAN OBESITAS PADA REMAJA DI SMA NEGERI 107 JAKARTA - Wardana Said, Reyhan (Poltekkes Kemenkes Bengkulu, 2025)
Obesity is overweight caused by the accumulation of excess fat in the body. This study aims to determine the relationship between stress levels, appetite, and eating patterns with the incidence of obesity in adolescents at SMA Negeri 107 Jakarta. This study is an observational quantitative study with a cross-sectional study. The population in this study were all female students in grades X and XI who attend SMAN 107 Jakarta with a sample size of 90 respondents obtained using a simple random sampling technique. The results of the study obtained from univariate analysis showed that 69 (76.7%) respondents were not obese and 21 (23.3%) respondents were obese. The results of the study using the Fisher's exact test showed a significant relationship between stress levels, appetite, eating patterns, and staple food consumption patterns with the incidence of obesity in adolescents at SMA Negeri 107 Jakarta (p-value <0.05). Keywords: adolescent, Appetite, Obesity, Diet, and Stress Levels